Improving Self-Protection Knowledge Against Sexual Abuse by Using Dreall Healthy and Animation Video - Adelia Pradita; Arie Kusumaningrum; Jum Natosba (Universitas Airlangga, 2018)
Introduction: The number of child sexual abuse cases in Indonesia are still high, including in Ogan Komering Ilir Regency, South Sumatera. One of the preventive effort that can be practiced is teaching them about children self-protection knowledge from sexual abuse through sexual education using appropriate methods and media, such as watching animated video and dreall healthy. The aim of this research was to determine difference in dreall healthy and animated video about sexual education toward children self-protection knowledge from sexual abuse.Methods: This research was a quantitative study and use quasi experiment design with pretest-postest group. Samples in this research were 40 children in dreall healthy group and 37 children in the animated video group, the samples were taken using purposive sampling technique. The data were collected by using questionnaire and data analysis was using paired t test and independent t test.Results: This research showed that there was difference in children self-protection knowledge from sexual abuse before and after sexual education with dreall healthy and animated video with p value 0.000 (α ≤0.05) and there was difference in children self-protection knowledge from sexual abuse between dreall healthy and animated video with p value 0.014 (α ≤0.05).Conclusion: Sexual education with dreall healthy is more effective to increase children self-protection knowledge because it can stimulate the children’s brain nerves so that their memory could be better. It was expected that parents, public health center staffs, and counselor in schools be able to provide sexual education as early as possible to the children.